PERANCANGAN MEDIA PROMOSI MOJOKERTO FANTASTIC PARK DENGAN TEKNIK DIGITAL IMAGING SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS DI MOJOKERTO - Budi, Agung Setiyo; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract:Mojokerto Fantastic Park is the first man-made tourist attractions in mojokerto reserved for Mojokerto not have far to look for tourist spots . The following rides are offered to the public is completed . But the absence of a media campaign that used by this sight , so many viewers who do not know the existence of this tourist spot . These attractions just rely on any occasion , this resulted in the information that will be delivered by Mojokerto Fantastic Park was not communicated to the audience . Therefore the aim of this scheme is directed at designing a media campaign Mojokerto Fantastic park with digital imaging techniques to increase brand awareness. This problem requires some effort to increase brand awareness , one is to design a media campaign to reintroduce Mojokerto Fantastic Garden while increasing the number of visitors.Keywords:Design, Promotion Media, Mojokerto Fantastic Park, Brand Awareness